Towards an international language for incontinence‐associated dermatitis (IAD): design and evaluation of psychometric properties of the Ghent Global IAD Categorization Tool (GLOBIAD) in 30 countries. (12th June 2018) - Beeckman, D.; Van den Bussche, K.; Alves, P.; Arnold Long, M.C.; Beele, H.; Ciprandi, G.; Coyer, F.; de Groot, T.; De Meyer, D.; Deschepper, E.; Dunk, A.M.; Fourie, A.; et al.
Summary: The best way to prevent and treat diaper dermatitis (nappy rash) in babies has been the topic of research for decades. However this skin problem can also occur in adults, where it is known as incontinence‐associated dermatitis (IAD). It is a specific type of irritant contact dermatitis ‐ a type of eczema caused when contact with something causes irritation (rather than an allergy), in this case prolonged contact of the skin with urine or faeces. It is hard to know exactly how many people suffer from IAD as there is not one set of internationally agreed diagnostic criteria (e.g. a list of specific symptoms and criteria that identify the disease) that help differentiate it from other skin disorders with similar symptoms, such as pressure ulcers. Ten different instruments / tools (meaning ways of diagnosing and ranking the severity of the disease) exist, but some are complex, and a single one is needed to make sure study results are comparable. Therefore, a group of 34 experts in 13 countries worked together to develop a tool that was started in 2015, called GLOBIAD. It was then translated into 14 different languages. Its accuracy was tested by asking 823 experts in 30 countries to categorize 34 photos of IAD using GLOBIAD to see if their results matched. The study found that the development of the GLOBIAD is a major step towards a better systematic assessment of IAD in clinical practice and research worldwide. However, further validation is needed. Abstract : Linked Article: Beeckman et al. Br J Dermatol 2018; 178 :1331–1340